Pyridoxine biosynthesis protein MoPdx1 affects the development and pathogenicity of Magnaporthe oryzae - Yang, Lina; Liu, Xiaohong; Wang, Jie; Li, Lianwei; Feng, Wanzhen; Ji, Zhaolin (Frontiers in Cellular and Infection Microbiology, 2023)
B vitamins are essential micro-organic compounds for the development of humans and animals. Vitamin B6 comprises a group of components including pyridoxine, pyridoxal, and pyridoxamine. In addition, vitamin B6 acts as the coenzymes in amino acid biosynthesis, decarboxylation, racemic reactions, and other biological processes. In this study, we found that the expressions of a gene encoding pyridoxine biosynthesis protein (PDX1) were significantly upregulated in the early infectious stages in M. oryzae. Furthermore, deletion of MoPDX1 slowed vegetative growth on different media, especially on MM media, and the growth defect was rescued when MoPdx1-protein was expressed in mutants strains and when commercial VB6 (pyridoxine) was added exogenously. However, VB6 content in different strains cultured in CM media has no significant difference, suggested that MoPdx1 was involved in de novo VB6 biosynthesis not in uptake process, and VB6 regulates the vegetative growth of M. oryzae. The ΔMopdx1 mutants presented abnormal appressorium turgor, slowed invasive growth and reduced virulence on rice seedlings and sheath cells. MoPdx1 was located in the cytoplasm and present in spore and germ tubes at 14 hours post inoculation (hpi) and then transferred into the appressorium at 24 hpi. Addition of VB6 in the conidial suspentions could rescue the defects of appressorium turgor pressure at 14 hpi or 24 hpi, invasive growth and pathogenicity of the MoPDX1 deletion mutants. Indicated that MoPdx1 affected the appressorium turgor pressure, invasive growth and virulence mainly depended on de novo VB6, and VB6 was biosynthesized in conidia, then transported into the appressorium, which play important roles in substances transportation from conidia to appressorium thus to regulate the appressorium turgor pressure. However, deletion of MoPDX1 did not affect the ability that scavenge ROS produced by rice cells, and the mutant strains were unable to activate host defense responses. In addition, co-immunoprecipitation (Co-IP) assays investigating potential MoPdx1-interacting proteins suggested that MoPdx1 might take part in multiple pathways, especially in the ribosome and in biosynthesis of some substances. These results indicate that vitamins are involved in the development and pathogenicity of M. oryzae.